COMPARATIVE ASSESSMENT OF BURNING OF CONIFEROUS AND DECIDUOUS BREEDS OF WOOD IN THE CONDITIONS OF NATURAL EMERGENCY SITUATIONS - Olga Vladimirovna Klimenko; Alexander Yuryevich Darzhaniya (Вестник Северо-Кавказского федерального университета)
Statistics of forest fires on the territory of the Russian Federation according to the Ministry of Emergency Situations of Russia is given, a scale of distribution of wood fund in Stavropol Krai on classes of fire danger, and also experiment during which the main features of burning of coniferous and deciduous trees were noted is described.